A Unique Population: Adipose-Resident Regulatory T Cells - Zeng, Qin; Sun, Xiaoxiao; Xiao, Liuling; Xie, Zhiguo; Bettini, Maria; Deng, Tuo (Frontiers in Immunology, 2018)
Regulatory T (Treg) cell is well known for its anti-inflammatory function in a variety of tissues in health and disease. Accordingly, Treg cells that reside in adipose tissue exhibit specific phenotypes. Their numbers are regulated by age, gender and environmental factors, such as diet and cold stimulation. Adipose-resident Treg cells have been suggested to be critical regulators of immune and metabolic microenvironment in adipose tissue, as well as involved in pathogenesis of obesity-related metabolic disorders. This review surveys existing information on adipose-resident Treg cells. We first describe the origin, phenotype and function of adipose-resident Treg cells. We then describe the major regulators of adipose-resident Treg cells, and discuss how the adipose-resident Treg cells are regulated in lean and obese conditions, especially in humans. Finally, we highlight their therapeutic potential in obesity-related disorders.